The Impact of Initial Vascular Access on Long-term Mortality in Hemodialysis Thai Patients - Kanin Thammavaranucupt (2022)
Background: End-stage kidney disease (ESKD) patients are significantly at risk of higher mortality than the general population. While cardiovascular disease and infection are the major causes of death in ESKD patients on hemodialysis (HD), the impact of vascular access type on long-term mortality in the Thai population remains unclear. Objective: To find an association between types of vascular access and long-term mortality in HD Thai patients. Methods: A multicenter, retrospective cohort of HD patients with a 55-month follow-up (November 2015 to December 2020) was conducted. Patients’ baseline characteristics, and HD profiles were reviewed. A logistic regression model and survival analysis were used to test the association and survival probability of each type of vascular access and mortality. Results: Of 196 HD patients over 55 months, the proportions of initial vascular access included 46.94% of arteriovenous fistula (AVF), 27.55% of arteriovenous graft (AVG), and 25.51% of tunneled dialysis catheter (TDC). The overall mean all-cause mortality in this cohort was 29.1%. Compared with AVF, TDC was associated with increased mortality (adjusted OR, 3.18; 95% CI, 1.37 - 7.37; P < .05) while the association between AVG and mortality was borderline significant (adjusted OR, 2.29; 95% CI, 0.96 - 5.46; P > .05). Conclusions: TDC as initial vascular access for incident HD Thai patients was associated with increased all-cause mortality at 55 months compared with functioning AVF.